KAJIAN HUKUM TERHADAP PERKAWINAN BEDA AGAMA DENGAN ADANYA YURISPRUDENSI MAHKAMAH AGUNG NO. 1400K/PDT/1986 - Karina Lizwary; Wahyuni Safitri (Law Department, University of Widya Gama Mahakam Samarinda, 2016)
Indonesia as pluralistic country with assorted tribe, race, language and culture and religion so that intermarriage occurs frequently. Intermarriage itself is not regulated in Law No. 1 of 1974 on Marriage and with the jurisprudence of the Supreme Court No. 1400 K / PDT / 1986 in the Jurisprudence decision does not prohibit the intermarriage so that the terms of a marriage is no longer an obstacle for those who want to perpetuate Interfaith Marriage. The issue of interfaith marriage arises in our country as a logical consequence of the recognition of Pancasila as the foundation of legal product, which contained therein